2004
DOI: 10.1530/eje.0.1510717
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of dehydroepiandrosterone sulphate (DHEAS) change in older men and women: the Rancho Bernardo Study

Abstract: Objective: To examine the age-related and sex-specific rates and determinants of change in endogenous dehydroepiandrosterone sulphate (DHEAS) levels in older community-dwelling adults, taking into account regression to the mean. Design: Prospective cohort study from Rancho Bernardo, California, USA. Methods: Plasma for DHEAS was collected at baseline and 10-14 years later from 242 men and 207 postmenopausal women (age range, 60 -77 years), who were not taking hormone therapy or corticosteroids. Age-related and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 50 publications
(34 reference statements)
6
22
1
Order By: Relevance
“…This is consistent with the present finding of an increase in IFN-γ plasma levels between middle-age and old-age in mouse lemurs. DHEA-S is accepted as a good biomarker of aging, as its levels progressively decrease with advancing age in various species, including humans (Baulieu et al, 2000;Tannenbaum et al, 2004). Such a decrease with age has previously been demonstrated in mouse lemurs , and it is confirmed by the present results.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the present finding of an increase in IFN-γ plasma levels between middle-age and old-age in mouse lemurs. DHEA-S is accepted as a good biomarker of aging, as its levels progressively decrease with advancing age in various species, including humans (Baulieu et al, 2000;Tannenbaum et al, 2004). Such a decrease with age has previously been demonstrated in mouse lemurs , and it is confirmed by the present results.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, DHEAS concentrations showed lower levels in women after the menopausal transition, corresponding with the reduction expected with aging 23,24 .…”
Section: Discussionmentioning
confidence: 53%
“…Plasma DHEA-S levels do not drop during the menopause transition, but decline with aging (1,2,20). A recent study has shown a positive correlation between DHEA-S levels and the duration of reactive hyperemia, another less specific marker of endothelial function compared to FMD, in young women (26±6 years old, n= 27) with polycystic ovary syndrome (21).…”
Section: Discussionmentioning
confidence: 96%